2008
DOI: 10.1002/asia.200800102
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Bulky Arylphosphanes by Rhodium‐Catalyzed Formal [2+2+2] Cycloaddition Reaction and Their Use as Ligands

Abstract: Treatment of 1-alkynylphosphane sulfides with 1,6- or 1,7-diynes in the presence of a cationic rhodium catalyst results in a formal [2+2+2] cycloaddition reaction to afford the corresponding aromatic phosphane sulfides. The aromatic rings formed in the cycloaddition naturally bear one or two substituents at the ortho positions to the phosphorus atom, which creates a sterically hindered environment around the phosphorus atom. The following desulfidation of the products is facile under radical conditions or with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 94 publications
0
2
0
Order By: Relevance
“…The synthesis of highly substituted, bulky arylphosphines and triarylarsines was accomplished by Yorimitsu and Oshima et al by using internal diynes and diphenylalkynyl thiophosphine or diphenyl(phenylethynyl)-arsine. 60 Their catalyst system comprised of [Rh(COD)Cl] 2 (16) with BINAP and AgBF 4 . In refluxing 1,2-dichloroethane, the AgBF 4 promotes anion exchange from 16 to provide the active cationic Rh(I)-complex.…”
Section: Rhodium(i)-complexes As Catalystsmentioning
confidence: 99%
“…The synthesis of highly substituted, bulky arylphosphines and triarylarsines was accomplished by Yorimitsu and Oshima et al by using internal diynes and diphenylalkynyl thiophosphine or diphenyl(phenylethynyl)-arsine. 60 Their catalyst system comprised of [Rh(COD)Cl] 2 (16) with BINAP and AgBF 4 . In refluxing 1,2-dichloroethane, the AgBF 4 promotes anion exchange from 16 to provide the active cationic Rh(I)-complex.…”
Section: Rhodium(i)-complexes As Catalystsmentioning
confidence: 99%
“…115 Both tris(trimethylsilyl)silane, (in the presence of a radical initiator in benzene), and tris(dimethylamino)phosphine have been used for the reduction to the phosphines (85) of the related sulfides obtained by a rhodium-catalysed formal [2 þ 2 þ 2] cycloaddition reaction between heteroatom-bridged dialkynes and alkynylphosphine sulfides. 116 The reduction of tertiary phosphine oxides with diisobutylaluminium hydride (DIBAL-H) has been the subject of a detailed study, resulting in a significant improvement in experimental protocols and making DIBAL-H a much more attractive reagent. 117 In a new development, it has been shown that alkylene bis(diphenylphosphine oxides) can be selectively reduced to the related bis(phosphine) monoxide under exceptionally mild conditions using a combination of triflic anhydride and a thiol.…”
Section: Bhmentioning
confidence: 99%